Challenges to effective management of public sector organizations in an institutionally corrupt society : a study of Nigeria - Nwokorie, Ethelbert (Vaasan yliopisto, 2017)
Tutkimus arvioi johtamisen vaikuttavuuden haasteita institutionaalisen korruption vaivaamassa yhteiskunnassa, tarkasteltavana tapauksenaan Nigeria. Se tarkastelee julkisen sektorin johtajien käyttäytymistä ja toimintaa näiden suorittaessa johtamistehtäviään. Tutkimuksen tarkoitus on osoittaa kuinka institutionaalinen korruptio vaikuttaa julkisten organisaatioiden johtamisen vaikuttavuuteen. Analyysi perustuu empiiriseen aineistoon, joka kerättiin haastattelemalla julkisten organisaatioiden johtajia Nigeriassa. Tutkimuksen teoreettisen viitekehyksen ydin muodostuu Luthansin ja kumppaneiden (1988) johtamistoimintojen analyysista, Mintzbergin (1980) johtamistyön luonteen analyysista sekä DuBrinin (2008) organisaatioiden matalaa vaikuttavuutta tuottavien tekijöiden analyysista. Nämä tutkimukset tuottavat näkemyksen siitä miten johtamistoiminta ja -käyttäytyminen kytkeytyvät organisaatioiden toiminnan vaikuttavuuteen tai sen puutteeseen. Tutkimus osoittaa, että institutionaalinen korruptio vaikuttaa kielteisesti monin tavoin nigerialaisten julkisten organisaatioiden johtajien toimintaan ja käyttäytymiseen. Se myös johtaa sellaisten muiden tekijöiden esiin nousemiseen, jotka myös madaltavat maan julkisten organisaatioiden toiminnan vaikuttavuutta. Johtamisen vaikuttavuutta parantavan toiminnan sijaan nigerialaiset julkisten organisaatioiden johtajat käyttävät aikaansa ja energiaansa sellaisiin toimiin, joiden vaikutus johtamisen vaikuttavuuteen on merkityksetöntä.

Despite the assumption that institutional corruption is the only cause of ineffectiveness of public sector organizations in an institutionally corrupt society, other factors that pose as challenge to effectiveness of public sector organizations go unnoticed due to the prevalence of institutional corruption. These factors negatively influence the behaviours of managers of public sector organizations, and how they perform their managerial functions. The effects of the influence on managerial performance make public sector organizations ineffective. With Nigeria as a case study, this research examined the challenges to effective management of public sector organizations in an institutionally corrupt society, by looking at the behaviours of managers of public sector organizations while performing their managerial functions. This research focused on unravelling how these factors affect the behaviours and functions of managers of public sector organizations in an institutionally corrupt society. Empirical data for this study was collected from interviews conducted with managers of public sector organizations in Nigeria. Luthans et al. study of managerial activities, Mintzberg study of nature of managerial work and DuBrin’s organizational ineffectiveness factors are the theoretical framework for this study. These studies provided an insight into the link between managerial behaviours/functions and organizational ineffectiveness. This research established that institutional corruption leads to the emergence of other factors that deepen ineffectiveness of public sector organizations in the country through erosion of ethical values of managers of public sector organizations. However, among other findings of this study that make public sector organizations in Nigeria ineffective, public sector managers do not perform managerial functions that have relative contribution to organizational effectiveness. Instead, they focus on managerial functions that only guarantee their career success.
Keywords: korruptio; lahjonta; fi=Julkisjohtaminen| sv=Offentligt ledarskap| en=Public Management|